The Impacts of Oil Price Shocks on Stock Market Volatility: Evidence from the G7 Countries - Andrea Bastianin; Francesca Conti; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2015)
We study the effects of crude oil price shocks on the stock market volatility of the G7 economies. We rely on a structural VAR model to identify the causes underlying the oil price shocks and gauge the differential impact that oil supply and oil demand innovations have on financial volatility. We show that stock market volatility does not respond to oil supply shocks. On the contrary, demand shocks impact significantly on the variability of the G7 stock markets.
Keywords: C32; C58; E44; Q41; Q43; 330; Volatility; Oil Price Shocks; Oil Price; Stock Prices; Structural VAR